Technological limitations in obtaining and using cellulose biocomposites - Masek, Anna; Kosmalska, Anna (Frontiers in Bioengineering and Biotechnology, 2022)
Among the many possible types of polymer composite materials, the most important are nanocomposites and biocomposites, which have received tremendous attention in recent years due to their unique properties. The fundamental benefits of using biocomposites as alternative materials to “petroleum-based” products are certainly shaping current development trends and setting directions for future research and applications of polymer composites. A dynamic growth of the production and sale of biocomposites is observed in the global market, which results not only from the growing interest and demand for this type of materials, but also due to the fact that for the developed and modified, thus improved materials, the area of their application is constantly expanding. Already today, polymer composites with plant raw materials are used in various sectors of the economy. In particular, this concerns the automotive and construction industries, as well as widely understood packaging. Bacterial cellulose, for example, also known as bionanocellulose, as a natural polymer with specific and unique properties, has been used extensively,primarily in numerous medical applications. Intensive research is also being carried out into composites with natural fibres composed mainly of organic compounds such as cellulose, hemicellulose and lignin. However, three aspects seem to be associated with the popularisation of biopolymers: performance, processing and cost. This article provides a brief overview of the topic under discussion. What can be the technological limitations considering the methods of obtaining polymer composites with the use of plant filler and the influence on their properties? What properties of cellulose constitute an important issue from the point of view of its applicability in polymers, in the context of compatibility with the polymer matrix and processability? What can be the ways of changing these properties through modifications, which may be crucial from the point of view of the development directions of biopolymers and bioplastics, whose further new applications will be related, among others, to the enhancement of properties? There still seems to be considerable potential to improve the cellulose material composites being produced, as well as to improve the efficiency of their manufacturing. Nevertheless, the material still needs to be well optimized before it can replace conventional materials at the industrial level in the near future. Typically, various studies discuss their comparison in terms of production, properties and highly demanding applications of plant or bacterial nanocellulose. Usually, aspects of each are described separately in the literature. In the present review, several important data are gathered in one place, providing a basis for comparing the types of cellulose described. On the one hand, this comparison aims to demonstrate the advantage of bacterial cellulose over plant cellulose, due to environmental protection and its unique properties. On the other hand, it aims to prepare a more comprehensive point of view that can objectively help in deciding which cellulosic raw material may be more suitable for a particular purpose, bacterial cellulose or plant cellulose.